2004
DOI: 10.1108/09604520410569784
|View full text |Cite
|
Sign up to set email alerts
|

Comfort your online customer: quality, trust and loyalty on the internet

Abstract: Users who downloaded this article also downloaded:Norizan Kassim, Nor Asiah Abdullah, (2010),"The effect of perceived service quality dimensions on customer satisfaction, trust, and loyalty in e-commerce settings: A cross cultural analysis", Asia Pacific Journal of Marketing and Logistics, Vol. For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
555
5
47

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 652 publications
(654 citation statements)
references
References 71 publications
47
555
5
47
Order By: Relevance
“…Especially online, it was pointed out that the lack of online consumer trust was the main barrier of consumer participation in e-commerce [38] and has been found to be one of the major obstacles to the popularity of internet transaction [39].…”
Section: Trustmentioning
confidence: 99%
“…Especially online, it was pointed out that the lack of online consumer trust was the main barrier of consumer participation in e-commerce [38] and has been found to be one of the major obstacles to the popularity of internet transaction [39].…”
Section: Trustmentioning
confidence: 99%
“…Trust mediates the relationship between interactivity and e-loyalty ). The finding of Ribbink et al (2004) and Kassim and Ismail (2009) identified that customization insignificantly affects trust in online buying. Deriving on this evidence, this paper implies that trustworthiness mediates the relationship between customer interface quality and customer e-loyalty.…”
Section: Development Of Hypothesesmentioning
confidence: 94%
“…In this sense, an individual consumer believes that internet is secure in transaction and transmitting the personal information data in the database of online company (Salisbury et al, 2001). Apart from that, privacy is acknowledged as an individual control and limits their information to the e-retailers on website (Ribbink, van Riel, Liljander, & Streukens, 2004). Privacy is also defined as the personal data protection from hackers without other e-consumer's knowledge (Deb & Chavali, 2009) such as the personal detail information (e.g., mobile number), total amount of every trip of online purchasing, and financial information (e.g., credit card's number).…”
Section: Literature Review E-loyaltymentioning
confidence: 99%
See 1 more Smart Citation
“…It is defined as the customer's perceived security and privacy when using the e-tailers services. Security concerns the risk of third parties obtaining critical information about the customer, whereas privacy relates to the concern about the potential misuse of personal information by marketers [3]. 3) Responsiveness.…”
Section: Literature Reviewmentioning
confidence: 99%